Digital services as a space for promoting social interests in conditions of intercountry gender differentiation - G. G. Sillaste; A. S. Arutyunyan (Цифровая социология)
The article investigates digital services as a tool for promoting social interests of Internet users. The analysis is conducted with consideration to the differences between countries and users’ gender. The criterion for selecting states was the human development index. Daily time spent on social networks in different countries is considered as an indicator. The study hypothesis is based on the assumption that the ability to promote social interests through digital services may be related to gender and skills in the sphere of information and communication technologies according to the typology of countries. The relevance of the study stems from the need to examine the impact of these services on the promotion of social interests in the context of gender differences between states. The article сonsiders various aspects of their use for the specified purpose, including a particularly thorough analysis of the emphasised differences in the application. The impact of digital services on the promotion of social interests within the framework of cross-country gender differentiation has also been studied. In addition, the influence of peculiarities of using these services by men and women on lobbying for this type of interests is discussed.